The role of religious loyalty in combating digital piracy: an Islamic perspective - Bayoumi, Kawthar A MA; Rosman, AS; Ripin, MN; Haron, Z; Zulkifli, Abdul Halim; Fadzillah, Nurrulhidayah (Usuli Faqih Research Centre, 2017)
Religiosity has been seen as a powerful determinant of human actions especially in situations of ethical dilemmas such as digital piracy. Thus, it has been addressed as a potential informal institution to curtail the phenomenon. However, previous research indicated a confounding influence of some contextual factors on the anticipated role of religious loyalty such as the dominant secular culture. As such, the main objective of this article is to investigate the role of religious loyalty in combating digital piracy from the Islamic perspective since loyalty is a core aspect of Muslim’s society as directly associated with faith. Additionally, this paper explores the contextual factors in Islamic countries that may influence the role of religious loyalty in fighting digital piracy. This study involved with qualitative data, gathered from journal articles and books, and then the data analysed using content analysis method. The analysis shows that integrating religion within the campaign toward copyright is potentially viable provided that other contextual factors are properly tackled